OBSERVACIONES SOBRE LARVAS DE PHOEBIS SENNAE AMPHITRITE (FEISTHAMEL) 1839 (LEPIDOPTERA) (Acta Entomológica Chilena, 2022)
The existence of two types of larvae is described for Phoebis sennae amphitrite; one type is sharp yellow,living on flowers of Sentía; the other type is deep green and living on the leaves of the same plant.Both types of larvae are perfectly homochromous with their respective substrate; it was showed thatthis difference in color does not correspond to a sexual dimorphism ñor that is the origin of sexualisolation.In the laboratory it was observed that it was possible to induce the change in color of the yellow larvae,when reared on green leaves of Senna, change that took place after the following moult; it was alsoobserved that while recently emerged females are able to copúlate, males on the contrary need at leasttwo days of activity after emergence in order to be active sexually.
Keywords: Larvae. Lepidoptera. Different types in one species